High anatomical accuracy of a novel high‐resolution wide‐band dielectric imaging system in cryoballoon‐based ablation. Issue 9 (28th July 2021) - Rottner, Laura; Nodorp, Milena; Jessica, Weimann; Schleberger, Ruben; Sinning, Christoph; Lemoine, Marc; Dinshaw, Leon; Münkler, Paula; Lin, Tina; Meyer, Christian; Reissmann, Bruno; Metzner, Andreas; et al.
Abstract: Purpose: Recently, a novel cardiac imaging system based on a wide‐band dielectric technology (KODEX‐EPD) was introduced to guide catheter ablation. The aim of the study was to evaluate this 3D wide‐band dielectric imaging system (WDIS) during cryoballoon (CB)‐based atrial fibrillation (AF) ablation focusing on accuracy of pulmonary vein (PV)‐anatomy. Methods: In consecutive patients with symptomatic AF, CB‐based ablation was performed in conjunction with the 3D WDIS. Selective PV‐angiographies were performed, and 3D anatomy of the left atrium (LA) and PVs using the 3D WDIS was created. The ostial diameters of the ipsilateral right‐sided and left‐sided PVs and ostial diameters of the right‐/left‐sided upper/lower PVs demonstrated by selective angiographies were analyzed and compared to 3D WDIS‐based PV visualization. Results: In 65 patients (42/65 (65%) male, age 65 ± 9 years, 29/65 (45%) paroxysmal AF) a total of 260 PVs were identified. Median ostial PV‐diameters for the ipsilateral left‐ and right‐sided PVs were 38 [34; 43] and 37 [34; 40.3] mm when assessed fluoroscopically and 40 [35.7; 43] and 39 [35.0; 43] mm as demonstrated by 3D WDIS. There was no statistically significant difference between both methods regarding PV‐diameter measurements. KODEX‐EPD overestimated fluoroscopy measurements by 1.08 mm (95% limits of agreement of ‐1.93 mm and 4.1 mm). Conclusion: The novel wide‐band dielectric 3D‐imaging system is feasible to create high‐resolution images of cardiac structures during CB ablation procedures and accurately visualizes PV‐anatomy.